A coalition of the (un)willing?: The convergence of landlord and renter interests in the "right to rent". Issue 2 (8th July 2019) - Amodu, Tola
Abstract : Purpose: The Immigration Act (2014) at Part 3 established a new regime with private landlords incurring penalties (and potentially criminal liability from 1 November 2016) if they allow a person disqualified, by reason of migration status, to reside in a property as their only or main home. Known colloquially as the "right to rent", the provisions restrict access to accommodation and impose onerous duties on landlords to check tenants' migration status. The purpose of this paper is to consider how a change in the emphasis of regulation introduced by the provisions, resulted in the coalescence of opposition by landlords and renters in a way that historically would have been unthinkable. Design/methodology/approach: Using the lens of Foucault's governmentality, it is possible to see how Government sought to shift the locus of control from itself to the landlord, which through its legislative and policy stance resulted in such fierce opposition as evidenced by the first instance challenge to the provisions in R ( Joint Council for the Welfare of Immigrants ) v SS for the Home Department [2019] EWHC 452 (Admin). Findings: The focus of regulation introduced by the provisions resulted in the coalescence of opposition by landlords and renters in a way that historically would have been unthinkable. Landlords and renters are usually thought of as being in opposition, but not so here. This may offer hope for more productive regulatory outcomes where both parties work together. It may also suggest that encroaching on the notion of private rights and interests in law could result in counterproductive consequences. Research limitations/implications: Unlike Foucault's notion of surveillance and control, governmentality shifts the emphasis from a hierarchical conception of government to practices including self (imposed) governance – with here, the landlord being required to act as a proxy for border agents. This suggests that there may exist boundaries beyond which, in a given context, it might be unwise for Government to step without adverse consequences. Foucault's ideas provide a starting point, but do not give us all of the answers. Practical implications: The coalescence of opposing actors can be a significant force to challenge government given the extent of their knowledge of the given context. It may also suggest a route to a more collaborative form of regulation. Originality/value: A novel theoretical take on an issue of concern raised by practitioners and interest groups alike.